Bark beetle effects on fuel profiles across a range of stand structures in Douglas‐fir forests of Greater Yellowstone. Issue 1 (1st January 2013) - Donato, Daniel C.; Harvey, Brian J.; Romme, William H.; Simard, Martin; Turner, Monica G.
Abstract : Consequences of bark beetle outbreaks for forest wildfire potential are receiving heightened attention, but little research has considered ecosystems with mixed‐severity fire regimes. Such forests are widespread, variable in stand structure, and often fuel limited, suggesting that beetle outbreaks could substantially alter fire potentials. We studied canopy and surface fuels in interior Douglas‐fir ( Pseudotsuga menziesii v. glauca ) forests in Greater Yellowstone, Wyoming, USA, to determine how fuel characteristics varied with time since outbreak of the Douglas‐fir beetle ( Dendroctonus pseudotsugae ). We sampled five stands in each of four outbreak stages, validated for pre‐outbreak similarity: green (undisturbed), red (1–3 yr), gray (4–14 yr), and silver (25–30 yr). General linear models were used to compare variation in fuel profiles associated with outbreak to variation associated with the range of stand structures (dense mesic forest to open xeric parkland) characteristic of interior Douglas‐fir forest. Beetle outbreak killed 38–83% of basal area within stands, generating a mix of live trees and snags over several years. Canopy fuel load and bulk density began declining in the red stage via needle drop and decreased by ∼50% by the silver stage. The dead portion of available canopy fuels peaked in the red stage at 41%. After accounting for background variation, there was little effect of beetle outbreak on surface fuels, with differences mainly in herbaceous biomass (50% greater in red stands) and coarse woody fuels (doubled in silver stands). Within‐stand spatial heterogeneity of fuels increased with time since outbreak, and surface‐to‐crown continuity decreased and remained low because of slow/sparse regeneration. Collectively, results suggest reduced fire potentials in post‐outbreak stands, particularly for crown fire after the red stage, although abundant coarse fuels in silver stands may increase burn residence time and heat release. Outbreak effects on fuels were comparable to background variation in stand structure. The net effect of beetle outbreak was to shift the structure of mesic closed‐canopy stands toward that of parklands, and to shift xeric parklands toward very sparse woodlands. This study highlights the importance of evaluating outbreak effects in the context of the wide structural variation inherent to many forest types in the absence of beetle disturbance.